Respiratory system intake and exhaust (New Jersey : Cambridge Educational, 2001)
Using the analogy of an automobile's system of fuel intake and exhaust, this program explores the makeup and funtions of the respiratory system. Topics include the processes of respiration; the organs involved in respiration; why cells need oxygen; structure and functions of the lungs; relationship between the brain and the respiratory system; and a detailed look at what's behind the simple act of breathing.
Keywords: Respiratory system